The adjuvant effects of high-molecule-weight polysaccharides purified from Antrodia cinnamomea on dendritic cell function and DNA vaccines. - Chi-Chen Lin; I-Hong Pan; Yi-Rong Li; Yi-Gen Pan; Ming-Kuem Lin; Yi-Huang Lu; Hsin-Chieh Wu; Ching-Liang Chu (PLoS ONE)
The biological activity of the edible basidiomycete Antrodia cinnamomea (AC) has been studied extensively. Many effects, such as anti-cancer, anti-inflammatory, and antioxidant activities, have been reported from either crude extracts or compounds isolated from AC. However, research addressing the function of AC in enhancing immunity is rare. The aim of the present study is to investigate the active components and the mechanism involved in the immunostimulatory effect of AC. We found that polysaccharides (PS) in the water extract of AC played a major role in dendritic cell (DC) activation, which is a critical leukocyte in initiating immune responses. We further size purified and identified that the high-molecular weight PS fraction (greater than 100 kDa) exhibited the activating effect. The AC high-molecular weight PSs (AC hmwPSs) promoted pro-inflammatory cytokine production by DCs and the maturation of DCs. In addition, DC-induced antigen-specific T cell activation and Th1 differentiation were increased by AC hmwPSs. In studying the molecular mechanism, we confirmed the activation of the MAPK and NF-κB pathways in DCs after AC hmwPSs treatment. Furthermore, we demonstrated that TLR2 and TLR4 are required for the stimulatory activity of AC hmwPSs on DCs. In a mouse tumor model, we demonstrated that AC hmwPSs enhanced the anti-tumor efficacy of the HER-2/neu DNA vaccine by facilitating specific Th1 responses. Thus, we conclude that hmwPSs are the major components of AC that stimulate DCs via the TLR2/TLR4 and NF-κB/MAPK signaling pathways. The AC hmwPSs have potential to be applied as adjuvants.